EXAMINING THE EFFECTS OF CONNECTIVE TISSUE MASSAGE ON PAIN AFTER THORACOTOMY - RANDOMIZED CONTROLLED TRIAL. - TEMEL AKSU, Neriman; ERDOĞAN, Abdullah (Turkish Journal of Physiotherapy Rehabilitation, 2024)
Purpose: The objective was evaluate the effect of a connective tissue massage on pain, applied analgesic amounts and length of hospitalization of the patients. Method: The study was a prospective, randomized, controlled clinical trial and conducted at a thoracic surgery department of university hospital. The patients were randomly allocated to 1 of 2 groups: a control group (n=27) and the experimental group (n=27). Standard medical treatment, care and pulmonary rehabilitation program were applied to both groups. In addition, a total of 5 sessions of connective tissue massage were applied to the experimental group. Pain level of the patients was evaluated at every 24 hours as of the zeroth postoperative day. VAS was used as a one-dimensional scale for pain assessment. Totally applied analgesic amounts and length of hospitalization of the patients were recorded. Results: There was no statistically significant difference between the experimental and control groups on the postoperative 0th and 1st days. A statistically significant difference was found between VAS averages on postoperative 2nd, 3rd, 4th, 5th, 6th and 7th days (p<0.001). Totally applied analgesic amounts of the the patients decreased significantly from the postoperative 2nd day (p<0.05). The length of hospital stay in the experimental group was short. Conclusions: The pain of the experimental group decreased significantly and their pain on the postoperative 7th day was quite low and therefore the need for analgesic drugs decreased significantly.